Comparison of Cervical Cytopathological Diagnosis Using Innovative Qi Brush and Traditional Cervex-Brush® Combi - Zou, Yuliang; Tuo, Xiaoqian; Wu, Lei; Liu, Yanli; Feng, Xue; Zhao, Lanbo; Han, Lu; Wang, Lei; Wang, Yiran; Hou, Huilian; Shi, Guizhi; Li, Qiling (Frontiers in Medicine, 2020)
Objectives: To compare the effectiveness between Qi brush and Cervex-Brush® Combi for the diagnosis of cervical lesions. Methods: After we registered a random-control clinical trial on the Chinese Clinical Trial Registry (No. XJTU1AF2017LSK-25), cervical cell samples were successively collected with both Qi brush and Cervex-Brush® Combi before undergoing colposcope. Colposcopy with biopsy was performed later. Histological diagnosis was regarded as the gold standard in this study. The following indices of the two brushes were compared: sampling degree of satisfaction and presence rate of metaplastic cells, together with sensitivity (Se), specificity (Sp), false positives (FP), false negatives (FN), positive predictive value (PPV), and negative predictive value (NPV). The kappa value was used to measure the inter-rater agreement of the Qi brush and Cervex-Brush® Combi in diagnosing cervical lesions. Results: In total, 74 patients were enrolled in this study. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the Qi brush were 57.14, 86.84, 76.19, and 73.33%, respectively. For the Cervex-Brush® Combi, they were 26.92, 88.89, 63.63, and 62.75%, respectively. In addition, the Qi brush had a higher satisfied sampling rate (89.19%) than the Cervex-Brush® Combi (83.78%), and the P-value was 0.336 using Chi-square test. The kappa value was 0.444, which indicated a medium agreement between these two brushes, and the sensitivity of the Qi brush was higher than that of the Cervex-Brush® Combi, with significant statistical difference (P = 0.039<0.05). Conclusions: The Qi brush was more effective than the Cervex-Brush® Combi for sampling and also had a slightly higher accuracy in diagnosing in cytology. In terms of social and economic benefits, the Qi brush may be a better cervical cytology collector.